CO2 solubility in aqueous N‐methylcyclohexylamine (MCA) and N‐cyclohexyl‐1, 3‐propanediamine (CHAP) solutions. Issue 3 (16th December 2022) - Tzirakis, Fragkiskos; Papadopoulos, Athanasios I.; Seferlis, Panos; Tsivintzelis, Ioannis
Abstract: N ‐methylcyclohexylamine (MCA) and N ‐cyclohexyl‐1, 3‐propanediamine (CHAP) have been suggested, in mixtures with lipophilic amines, as potential phase change solvents for CO2 capture applications, and subsequently studied as promising alternatives to monoethanolamine (MEA) for minimizing the desorber's energy requirements. In this study, new high pressure experimental data were obtained for the solubility of CO2 in aqueous solutions containing MCA or CHAP at 313 and 333 K. The obtained data were used to parameterize the modified Kent–Eisenberg model. In this direction, CHAP was modeled assuming a "principle of independent reactivity, " that is, that the reactivity of each amine group does not depend on the potential reaction of the other one. It was shown that through this approach the model can be successfully applied to diamines using the relevant equations of amine mixtures.